The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1542/peds.2021-052201
|View full text |Cite|
|
Sign up to set email alerts
|

Medical Admissions Among Adolescents With Eating Disorders During the COVID-19 Pandemic

Abstract: This study examines medical admission patterns among adolescents with restrictive eating disorders before and after the onset of the COVID-19 pandemic. What's Known on This SubjectLimited data suggest the COVID-19 pandemic has been associated with worsening mental health outcomes, including worsening symptoms of eating disorders. Little is known about the potential effects of the pandemic on medical admission patterns among adolescents with eating disorders. What This Study AddsMedical admissions among adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
117
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 30 publications
13
117
4
Order By: Relevance
“…Our study con rms the onset of an "epidemic within the pandemic" [31], characterized by an increased severity of ED during the COVID-19 era, which is congruous with other reports [25,26]. As depicted in Figure 2, the epidemiological trend of ED admissions during the COVID-19 pandemic shows an overall increase compared to the previous pre COVID-19 year, with peaks and troughs of incidence that may be linked to emergency measures adopted by the Italian government such as school closures (the rst of which was announced on February 23rd, 2020) and their consequences: distance learning, home con nement, lifestyle changes [32].…”
Section: Discussionsupporting
confidence: 60%
“…Our study con rms the onset of an "epidemic within the pandemic" [31], characterized by an increased severity of ED during the COVID-19 era, which is congruous with other reports [25,26]. As depicted in Figure 2, the epidemiological trend of ED admissions during the COVID-19 pandemic shows an overall increase compared to the previous pre COVID-19 year, with peaks and troughs of incidence that may be linked to emergency measures adopted by the Italian government such as school closures (the rst of which was announced on February 23rd, 2020) and their consequences: distance learning, home con nement, lifestyle changes [32].…”
Section: Discussionsupporting
confidence: 60%
“…Following declines in weekly visits associated with MHCs among children and adolescents aged 0-17 years, during 2020 compared with 2019, weekly ED visits for MHCs overall and for specific MHCs varied by age and sex during 2021 and in January 2022. The current trends in the number and proportion of MHC-related ED visits, along with previous research (1,2,(4)(5)(6)(7)(8), indicate that the mental health effects of the pandemic might be particularly high among adolescent girls.…”
Section: Discussionmentioning
confidence: 80%
“…Increases in weekly visits for eating and tic disorders for females, and particularly among adolescent females aged 12-17 years during 2020, 2021, and in January 2022, could represent an overall increase in distress among females during the pandemic. Both eating and tic disorders can co-occur with anxiety, depression, and OCD (1,(4)(5)(6)(7). Eating disorders can be triggered by pandemic-related risk factors (e.g., lack of structure in daily routine, emotional distress, and changes in food availability) or exacerbated by reduced access to mental health care during the pandemic (4,5).…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Similarly, a recent single-center study in the US reported a doubling of hospitalizations for restrictive eating disorders during the COVID-19 pandemic. 14 To date, the association between the pandemic and its confinement measures and the genesis of new-onset anorexia nervosa or atypical anorexia nervosa has not been studied. In this study, we sought to assess the incidence and severity of newly diagnosed anorexia nervosa or atypical anorexia nervosa in a national sample of children and adolescents before and during the first wave of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%